KOMUNITAS BURUNG DI HUTAN LINDUNG GUNGUNG MASARANG - Otis Warwer; Johny S. Tasirin; Wawan Nurmawan (COCOS, 2018)
ABSTRACT According to Dias (2006) Bird communities are groups of individuals of several species who live together in the same space and time. Complex and heterogeneous vegetation structures will increase diversity in a habitat, which is thought to increase the diversity of birds in a community. The purpose of this study was to study bird communities in Gunung Masarang Protection Forest, Tomohon City. The study was conducted in June to July 2018 in the Mount Masarang Protection Forest. Data retrieval is done by meode count points (count points). The results showed that there were 47 species of birds from 24 families in Gunung Masarang Protection Forest, with 19 species of Endemic Sulawesi and 2 species protected by LHK 92/2018 Candy with medium species diversity H '= 2.66 and evenness value E = 0.61. Keywords: Birds, Bird Communities, Mount Masarang Protected Forest